Building vs. Rebuilding Epidermis: Comparison Embryonic Development and Adult Wound Repair - Park, Sangbum (Frontiers in Cell and Developmental Biology, 2022)
Wound repair is essential to restore tissue function through the rebuilding of pre-existing structures. The repair process involves the re-formation of tissue, which was originally generated by embryonic development, with as similar a structure as possible. Therefore, these two processes share many similarities in terms of creating tissue architecture. However, fundamental differences still exist, such as differences in the cellular components, the status of neighboring tissues, and the surrounding environment. Recent advances in single-cell transcriptomics, in vivo lineage tracing, and intravital imaging revealed subpopulations, long-term cell fates and dynamic behaviors in live animals that were not detectable previously. This review highlights similarities and differences between adult wound repair and embryonic tissue development with a particular emphasis on the epidermis of the skin.